Traceability, Validation and Measurement Uncertainty in Chemistry: Vol. 3 Practical Examples - Hrastelj, Nineta; Bettencourt da Silva, Ricardo (Springer International Publishing : Imprint: Springer, 2019)
This book presents worked examples of five analytical procedures. These practical examples address traceability, validation and measurement uncertainty aspects in a systematic and consistent way, and cover applications in the analysis of water, food, as well as ores and minerals. This concept is based on the experiences of the TrainMiCc program, in which more than 9000 laboratory professionals all over Europe have participated.